EFFECT OF CULTURE MEDIA AND TEMPERATURE ON MYCELIAL GROWTH AND SPORULATION OF TION OF TION OF Myrothecium roridum, THE LEAF , THE LEAF SPOT AND STEM NECROSIS PATHOGEN OF COFFEE SEEDLINGS THOGEN OF COFFEE SEEDLINGS - A. P. RANJINI; RAJA NAIKA (The Bioscan, 2018)
The fungus Myrothecium roridum is a potential pathogen which causes leaf spot and stem necrosis on coffee seedlings in the nursery. In vitro studies were carried out to find out the best culture medium for the better growth and sporulation of the fungus. Nine different media were used for the studies. They are viz., Potato Dextrose Agar (PDA), Potato Sucrose Agar (PSA), Malt Extract Agar (MEA), Yeast Extract Agar (YEA), Czapekdox Agar (CZA), Hansen’s Agar (HA), Potato Carrot Agar (PCA), Glucose Peptone Agar (GPA) and a semi artificial medium-Coffee Leaf Extract Agar (CLEA). Growth and sporulation of the pathogen was also studied at different temperature levels viz., 10, 15, 20, 25, 30 and 35ºC. The study indicated that Coffee Leaf Extract Agar is the most suitable medium and recorded maximum radial growth of 88.16 mm followed by Potato Dextrose Agar (74.83 mm) 15 days after incubation (DAI), as the better growth media for culturing the fungus M. roridum. Highest sporulation was observed in PCA and YEA. The present study also clearly indicated that 25ºC is the optimum temperature and recorded maximum radial growth of 89.37 mm 15 DAI and sporulation of the fungus was at the maximum level.